The Phenotype of Monocytes in Anterior Uveitis Depends on the HLA-B27 Status - Kasper, Maren; Walscheid, Karoline; Laffer, Björn; Bauer, Dirk; Busch, Martin; Wildschütz, Lena; Wang, Bo; Loser, Karin; Vogl, Thomas; Grajewski, Rafael S.; Langmann, Thomas; Heiligenhaus, Arnd (Frontiers in Immunology, 2018)
HLA-B27 is the allele most frequently associated with human anterior uveitis. The majority of HLA-B27-positive (acute anterior uveitis, AAU) patients develop clinically distinct symptoms with acute symptomatic onset of flare and a recurrent disease course characterized by a massive cellular ocular infiltrate during uveitis relapse. In contrast, uveitis in HLA-B27-negative (idiopathic anterior uveitis, IAU) patients tends to develop a clinically less fulminant, more chronic and typically asymptomatic disease course. In order to analyze systemic immune responses in the different uveitis entities, we analyzed peripheral blood cells by flow cytometry. In addition, as a pro-inflammatory biomarker serum S100A8/A9 levels were quantified by ELISA from patients with AAU (n=27) and IAU (n=21), and in healthy controls (n=30). Data were obtained either during active uveitis flare or after 3 months of inactivity. IAU patients showed a transiently increased frequency of CD56- and CD163-positive monocytes and of both granulocytic MDSC and Th17 cells during active uveitis. In contrast, AAU patients showed an elevated frequency of monocytes, activated T cells, and elevated S100A8/A9 serum levels during clinically quiescent disease. The differentially regulated response of both innate and adaptive immune cells in the blood may be related to the clinically distinct characteristics of the two different uveitis entities.